Liberty and Empire : British Radical Solutions to the American Problem, 1774-1776 - Toohey, Robert E. (Book collections on Project MUSE., 1978)
Though little known to most students of the American Revolution, the British Radicals of the 1770s championed the rights of Americans while advocating parliamentary reform and denouncing British colonial policies. Outspoken, eloquent, and innovative, the Radicals encouraged the American cause. They voiced ideas on liberty and empire that would echo through American revolutionary documents. Liberty and Empire focuses on five British Radicals. The farsighted John Cartwright's ideas of reformation anticipated the Commonwealth of Nations. James Burgh's treatise on parliamentary reform became a cla.